2023
DOI: 10.3390/healthcare11070983
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with the Use of Complementary and Alternative Medicine/Therapy among United States Adults with Asthma

Abstract: This article examined the sociodemographic and health-related factors associated with the use of complementary and alternative medicine/therapy (CAM) among adults with current asthma in the United States. We used data from 76,802 adults aged 18 years and above from the 2012–2019 Behavioral Risk Factor Surveillance System (BRFSS) Asthma Call-back Survey (ACBS) cycles. Weighted binary and multinomial logistic regression was used to examine the association of these factors with ever CAM use and the number of CAM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…Educational qualification and income did not positively associate with CAM use in this study. This is similar to the finding in another study done on asthmatic subjects in United States where the income status of the participants did not associate with the use of CAM 48 . Similarly, a recent multicentre study found that both the lowest and highest socioeconomic groups in China demonstrated an increased preference for CAM 49 .…”
Section: Discussionsupporting
confidence: 90%
“…Educational qualification and income did not positively associate with CAM use in this study. This is similar to the finding in another study done on asthmatic subjects in United States where the income status of the participants did not associate with the use of CAM 48 . Similarly, a recent multicentre study found that both the lowest and highest socioeconomic groups in China demonstrated an increased preference for CAM 49 .…”
Section: Discussionsupporting
confidence: 90%
“…It has been reported that CAM can help children decrease the annual uptake of influenza vaccination. 132 , 133 Acupuncture therapy, one of the most commonly used alternative medicine tools, cannot form a standard guideline protocol due to the small sample size and significant bias of the randomized controlled trials of acupuncture for asthma, making it difficult to assess the quality of research on acupuncture. 134 Therefore, more high-quality studies are needed to clarify the duration of acupuncture, improvement of clinical symptoms, adverse effects, and even reactions related to immune mechanisms.…”
Section: Discussionmentioning
confidence: 99%